Etica e impresa: come e perché 'ritornare' a Polanyi - La Rosa, Michele (Business and Ethic: why should we go back to Polanyi?, 2008)
The essay, after trying to do a synthesis of today's debate about business and ethics, proposes to return to Karl Polanyi starting from a different meaning of the three founding principles proposed by the author (exchange, reciprocity and redistribution).
Keywords: business ethics; business people; essay (literary form); professional ethics

Mercato: fatto o valore? Oltre la dicotomia - Rovelli, Riccardo (Market: fact or values? Beyond dichotomy!, 2008)
Economists are fond of proposing market solutions for many problems of resource allocation, while scholars from other social disciplines are often less inclined to adopt such solutions. In this essay I interpret the dichotomy for/against the market in the light of the one between neoclassical economics and the socio-anthropological tradition which originates with Karl Polanyi. In the first part, I suggest that this dichotomy runs in parallel to the one between facts and, which is typical of (neo)positivist thought. This dichotomy, which has been analyzed by Hilary Putnam, also reflects the self-portrait of neoclassical economics, as it has been proposed by Pareto and Robbins. Following this perspective in the second part I suggest on the one hand that the work of Polanyi should be interpreted as a reaction to neoclassical economics, but on the other hand it is also based on an incorrect interpretation of both facts and ideas in the history of ancient societies. Finally I notice that, although recent researches confirm that ancient societies should be interpreted as "conglomerations of interdependent markets" (thus following Temin against Polanyi and Finley), the presence and relevance of markets does not justify an under-socialized interpretation of ancient market economies: on the contrary, as it was well clear to many scholars, in a tradition that loosely connects Homer with Adam Smith, markets are and should be interpreted as value-laden facts. In the conclusion I discuss some implications of this view for the analysis of contemporary society.
Keywords: PUTNAM, Hilary, 1926-2016; SMITH, Adam, 1723-1790; economists; feasibility studies; markets - social aspects; neoclassical economics; neoclassical school of economics; resource allocation

Društvo I (ili) Tržište -- Sociološka Konceptualizacija Procesa Marketizacije Društva - Peračković, Krešimir (Gesellschaft und (oder) Markt. Eine soziologische Konzeptualisierung des Prozesses der Gesellschaftsmarketisierung., 2008)
The main goal of this work was to theoretically conceptualise the process of marketisation which designates the transformation of society into a market economy and social relations into market relations. The starting point is first the comparative analysis of the definitions of the term market by some classic authors (Smith, Marx, Weber, Durkheim and Parsons), each of whom define it from their perspective as a monetary mechanism of exchange in the economic sphere of social activity. In the second chapter K. Polanyi's theory of social transformation is presented, in which he is the first to state that the principle of market self-regulation has become the fundamental feature of modern society. Analysed in the third chapter is the market economy society model of D. Slater and F. Tonkiss, who claim that the process of marketisation in the most developed countries has already been completed and that today's society has already become a market society. The paper also presents in short the theory of marketing neglected in sociological literature, the main concept of market economy as a rational system of research and planning, which is currently not only applied in the economy but also in politics and culture. A special chapter is devoted to commodification, a process that concretises on a micro level the goals of marketisation, implying the transformation of nature, things, people, relations, meanings and immaterial resources into market commodities. The ultimate result of the marketisation and commmodification processes in a market society becomes evident in Rifkin's ominous hypothesis that all human life has become an experience to pay for, which is also the topic of the last chapter. (English)
Keywords: Kommodifizierung; Marketisierung; Markt; Marktgesellschaft; Marktverhältnisse; capitalism; commodification; comparative studies; definitions; komodifikacija; market; market relations; market society; marketing; marketisation; marketizacija; research; socioeconomics; tržišni odnosi; tržišno društvo; tržište

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Keywords: ARENDT, Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks

Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER, Max, 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

The market and the nation: Austrian (dis)agreements - Karner, Christian (Social Identities, 2008)
This article relates contemporary Austria's much-discussed and internally contested identity politics to transnational socio-economic transformations and their far-reaching local/national effects. A qualitative analysis of (wide-ranging contributions to) current debates on the environment, food production, climate change, social inequality and welfare, higher education, art, migration, and unemployment reveals a recurring pre-occupation with expanding/encroaching markets, their advocated limits, assumed costs or promises. The negotiation of national identities is shown to unfold in relation to three inter-related phenomena: first, widening commodification; second, what Karl Polanyi termed the 'double-movement' between 'dis-embedded' economics and political counter-assertions; third, competing ideological visions of the relationship between economic activity/market forces and social order, group boundaries, solidarities and hence exclusions/inclusions.
Keywords: Austria; commodification; economic anthropology; globalization; identity politics; markets; migration; nationalism; political science; public contracts; qualitative research; social order; socioeconomics

Beyond Ethnic Entrepreneurship: An Embedded Market Approach to Group Affiliation in American Enterprise - Valdez, Zulema (Race, Gender & Class, 2008)
The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership and the particular structural conditions of the economy and society combine to facilitate ethnic enterprise. Yet, this model remains largely descriptive and imprecise with respect to how and why class and ethnic resources and structural opportunity matter. Furthermore, this approach neglects to consider the likelihood that other non-ethnic social groupings distinct from ethnicity, such as those rooted in class, gender, or racial group affiliation, might also influence entrepreneurship. To address these concerns, this article introduces an "embedded market" (Block, 2003; Polanyi, 1944) approach that situates the role of group affiliation within the context of American capitalism. This approach begins with the premise that the role of group affiliation in economic action originates in and is maintained and reproduced by the social structure of the capitalist system in which it is embedded. Specifically, the embedded market approach reconsiders ethnic group membership, along with other politically-influenced social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief in the form of social capital to augment market uncertainty in the modern market economy. This article uses the case of Latina domésticas to demonstrate the compensatory role of group affiliation and its corollary social capital in facilitating ethnic and "non-ethnic" enterprise in American capitalism.
Keywords: United States; business enterprises - United States; capitalism; class; doméstica; embedded market; entrepreneurship; ethnic entrepreneurship; ethnic groups; gender; race; social capital; social classes

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Keywords: POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations

Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Keywords: formalist; substantivist

Polanyi's Double Movement: A Critical Reappraisal - Maertens, Eppo (Social Thought & Research, 2008)
The article offers a critical reappraisal of Karl Polanyi's claim that the restructuring of the economy based on the ideals of the self-regulating market inevitably leads society to reassert itself against the commodification of land, labour and money. Dubbed as the "double movement," the author focuses his reappraisal on the two aspects of the movement. The first refers to the push for free market reforms by various groups in society, and the second refers to the counter-movements that he argues necessarily and spontaneously mobilize against it. In this paper, he argues that the first aspect is an area that deserves further attention, both from those who wish to apply his ideas as well as from those who wish to challenge them.
Keywords: central economic planning; commodification; critique; double movement; dual economy; economic structure; free enterprise; market ideology; markets; public welfare

The Great Transformation: The Political and Economic Origins of Our Time - Meier, Brian (Social Thought & Research, 2008)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polayni.
Keywords: Great Transformation, The (Book); book review; economics; nonfiction

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Keywords: criticism of economism; formal economy; general economics

Third Way Labor Law Reform in Chile - Rosado Marzan, Cesar F. (Conference Papers -- Law & Society, 2008)
Latin America is currently undergoing Karl Polanyi's "double movement" at full swing, as most governments of the region are currently experimenting with policies that defy the neoliberal orthodoxy that has been reigning there for almost three decades. One of such governments has been the center-left Concertación governments of Chile, which have been elected since the restoration of democracy in 1990. In addition to poverty alleviation programs, Concertación has been in an ongoing process of reforming the country's labor laws, attempting to restore some of the labor rights existing prior to the 1973 coup, as well as creating new rights and institutions. The labor inspectorate has been strengthened and reformed under the framework of "Latin" systems of labor inspections, which are pedagogical rather than punitive in orientation. Labor courts are also being radically bolstered, providing workers with a renewed legal avenue to enforce their rights. Although the reforms fall short of full restoration of trade union rights, namely national collective bargaining, they do point to a clear break with the "stateless" regulatory, neoliberal model that Chile was once associated with and provide symbolic and intellectual fodder for further reforms in the country and beyond. ..PAT.-Unpublished Manuscript
Keywords: Chile; Latin America; labor laws & legislation; labour laws & legislation; law reform; mixed economy

Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
Keywords: capitalisme; fascisme; marché; socialisme

Group Affiliation and Market Embeddedness in American Enterprise - Valdez, Zulema (Conference Papers -- American Sociological Association, 2008)
In this article, Polanyi's (1944) notion of society as constituted by three forms of economic integration (market exchange, reciprocity, and redistribution) is applied to entrepreneurship. In advanced capitalism, the market-exchange relationship is the dominant form of economic integration; secondary relationships of reciprocity and redistribution, however, co-exist alongside relations of market exchange. Following Polanyi (1944), this article introduces an "embedded market" approach to enterprise. The embedded market approach considers the differential effects of primary and secondary relationships on entrepreneurial outcomes. The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership is essential for entrepreneurial success, as measured by participation and earnings. The embedded market approach reconsiders ethnic group membership, along with other politically-influenced human social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief from market uncertainty in the form of social capital. Ultimately, the embedded market approach provides a systematic and comprehensive approach to understanding the role of group affiliation in facilitating ethnic and "non-ethnic" enterprise in America.
Keywords: Latino/a Sociology; United States; class and gender; commercial policy; entrepreneurship; ethnic entrepreneurship; inequality; international economic integration; new business enterprises; race